The Adaptation, Implementation, and Performance Evaluation of Intake24, a Digital 24-h Dietary Recall Tool for South Asian Populations: The South Asia Biobank - Divya Bhagtani; Birdem Amoutzopoulos; Toni Steer; David Collins; Suzanna Abraham; Bridget A Holmes; Baldeesh K Rai; Rajendra Pradeepa; Sara Mahmood; Abu Ahmed Shamim; Poorvee Mathur; Lathika Athauda; et al. (Current Developments in Nutrition)
Background: South Asia’s diverse food supply, food preparations, and eating behaviors require dietary instruments that reflect the consumption patterns of South Asians to enable context specific dietary assessment. Such instruments are not readily available for detailed dietary assessment at scale in South Asia. Objectives: We describe the adaptation, implementation, and performance evaluation of Intake24, an open-source digital 24-h dietary recall tool, for dietary assessment in South Asia. Methods: We adapted Intake24 for dietary assessment in the South Asia Biobank (SAB), a large population-based study in Bangladesh, India, Pakistan, and Sri Lanka. Intake24 adaptation encompassed the development of a South Asian food database with commonly consumed foods, linked with corresponding portion sizes, food probes, and nutrient information. Trained interviewers conducted the 24-h recalls. Performance of Intake24 was evaluated in 29,113 South Asian adults. Results: The South Asia Intake24 food database included 2283 items and demonstrated good coverage of foods consumed across SAB regions. Median recall completion time was 13 min. Quality control metrics showed 99% of recalls included >8 items and 8% had missing foods. Median energy intake was higher in younger individuals compared to older, and in males compared to females. Underweight participants reported lower energy intake, with no discernible difference across other BMI categories. Conclusions: Intake24 enables comprehensive dietary assessment in regions of South Asia and will facilitate the analysis of dietary patterns, food and nutrient intake, and their relationship with health outcomes among South Asians.